PENGARUH PARTISIPASI DALAM PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJERIAL DAN MOTIVASI SEBAGAI VARIABEL INTERVENING - Mohamad Natsir (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2010)
The aim of the research 16 test the influence of participating in prepare budget organisation on managerial performance and motivation as a intervening variable. The respondents are managers or head of department that prepare firm budget in manufactured listed firms. The hypothesis test that used is SEM. The result show that participation has positive influence on motivation. Participation also has positive influence on managerial performance and motivation has positive influence on managerial performance.Keyword : Budgetary, Performace and Motivation